Cationic and Neutral (Ar‐BIAN)Copper(I) Complexes Containing Phosphane and Arsane Ancillary Ligands: Synthesis, Molecular Structure and Catalytic Behaviour in Cycloaddition Reactions of Azides and Alkynes (Eur. J. Inorg. Chem. 9/2013). Issue 9 (12th March 2013) - Li, Lidong; Lopes, Patrícia S.; Figueira, Cláudia A.; Gomes, Clara S. B.; Duarte, M. Teresa; Rosa, Vitor; Fliedel, Christophe; Avilés, Teresa; Gomes, Pedro T.
Abstract : The cover picture shows the X‐ray structure of one of the (aryl‐BIAN)copper(I) complexes synthesised in this work, which is reported along with a good number of other new cationic and neutral (aryl‐BIAN)copper(I) complexes containing phosphane and arsane ancillary ligands. Their catalytic activity towards the azide–alkyne Huisgen cycloaddition reaction (CuAAC) was studied. The picture background represents the 25th of April Bridge, one of the icons of the city of Lisbon, but also symbolises the collaboration between the two research teams, working at different universities that are located on the two banks of the river Tejo (Tagus). Details are discussed in the article by T. Avils, P. T. Gomes et al. on p. 1404 ff.